Communicate to inspire a guide for leaders - Murray, Kevin 1928- (Kogan Page, 2014)
" Communicate to Inspire answers some of the key practical questions for becoming a better leader, such as: "How do you learn to be yourself, better?" and "What should you examine and how should you articulate your own purpose and values?" Kevin Murray presents a model that charts the leadership process and draws stories from his experience coaching leaders. This book offers principles of leadership communication that address: how to become more audience-centric; how to emphasize values; how to focus on the people leaders need to inspire; what methods and tools to use to try to see the world through their eyes and address their needs; and mastering the art of public speaking. Communicate to Inspire uses charts and information gathered from dozens of successful training programs to determine how to turn a department, division or company into a better listening, faster responding, more innovative entity, just by holding more and better structured conversations"--Provided by publisher.